The Role Of Islamic Religious Education Teachers In Addressing Social Issues Among Ninth Grade Students At Smp Negeri 2 Tomia - Andini Pratiwi; Abdul Rahim; Sulasri (Dirasah: Jurnal Pendidikan Islam, 2025)
This research This study aims to examine the efforts of Islamic Religious Education (PAI) teachers in overcoming social problems of students in class IX at SMP Negeri 2 Tomia. Overcoming social problems of ninth grade students at SMP Negeri 2 Tomia. Background of this research is the importance of the role of Islamic Education not only as a teaching of religious values, but also as a means of moral and social development. religious values, but also as a means of moral and social development of students. students. PAI teachers play an active role in providing guidance, character building, as well as applying learning methods that motivate and teach students to positive behavior. positive behavior. Collaborative efforts between teachers, parents, and the school environment are very important to create a conducive atmosphere for students' development. school environment is very important to create a conducive atmosphere for the development of students' character development and the quality of students' social interactions. This research provides practical recommendations for teachers and schools in enhancing the role of PAI as a medium for social and moral development of students. as a medium for social and moral development of students.